PEMANFAATAN KOMPOS PADA LAHAN KRITIS UNTUK MENUNJANG PRODUKSI BAWANG MERAH, KACANG TANAH, DAN KEDELE DI KABUPATEN MINAHASA UTARA - Supit, Joice M.J.; Kamagi, Yani E.B.; Kumolontang, Wiesje J. (Universitas Sam Ratulangi, 2016)
ABSTRACT The experiment pot of the effect compost in the critical land on the production onions, peanuts, and soybeans, the goal is to get organic agricultural production and determine the optimal dose of compost for plant onions, peanuts and soybeans. Before the experiment of compost treatment was conducted the compost and soil as media plant to analyse the chemical properties. After the experiment of compost treatment was conducted the soil as media plant to analyse the chemical properties. The experiment design of methode was used complate randamized design (CRD) with the five treatment compost and four replication. Dosage of compost consists of 0 tonnes/ha (0 g/pot) as a control, 30 tonnes /ha (75 g /pot); 60 tonnes/ha (150 g/pot); 90 tonnes/ha (225 g/pot), and 120 tonnes/ha (300 g/pot). The parameter were observed wet weight of plants, quantity and weight beet the production plant of onions; wet weight of plants, quantity and weight of pod pea and seed the production plant of peanuts and soyabeans. The data of analysis was used the analysis of variance (Anova) and the least significant difference (LSD). The results showed that treatment of compost very significant effect on the growth and production of plant onions, peanuts and soybeans. Treatment compost 90 tonnes/ha (225 g/pot) provide growth and yield of plant onion, peanuts, and soybeans maximum. Keywords: compost, onion, peanut, soybean, critical land